Teaching moral dilemma in the COVID-19 pandemic - Hartono, Yudi (Master Program of Social Science Education of Universitas Negeri Padang, Indonesia, 2023)
The COVID-19 pandemic has caused various moral dilemmas. In Indonesia, there is a dilemma of whether to stay at home or go outside for work, whether to study at school or from home, whether to return home or not on holidays for migrants and whether to pray from home or at the place of worship. These various dilemmas can be used as materials or learning sources for students. They can learn to make moral decisions based on factual arguments through value clarification techniques by utilizing information and communication technology. The implementation of this model can provide students with a good learning experience in making a rational moral decision based on the facts revealed by the students’ active participation in online learning. This model can also be applied in other situations when people are faced with various dilemmas.